1976
DOI: 10.1042/bj1540193
|View full text |Cite
|
Sign up to set email alerts
|

The topographical location and unique nature of a glucokinase associated with the Golgi apparatus of rat liver

Abstract: A particulate glucokinase was recovered in the Golgi-rich fraction of rat liver prepared by the method of Morre [Methods Enzymol. (1971) 22, 130-148], thus extending the demonstration by Berthillier et al. [Biochim. Biophys. Acta (1973) 293, 370-378] of particulate glucokinase activity in a microsomal subfraction that showed enrichment in Golgi characteristics. The purity of this fraction was examined and it was then subjected to several treatments, the action of Triton X-100, freezing and thawing, and sonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A Golgi form of GK has previously been reported in the liver. That study also showed that the hepatic Golgi GK did not cross-react with an antiserum specific for cytoplasmic GK (Berthillier et al 1976).…”
Section: Discussionmentioning
confidence: 86%
“…A Golgi form of GK has previously been reported in the liver. That study also showed that the hepatic Golgi GK did not cross-react with an antiserum specific for cytoplasmic GK (Berthillier et al 1976).…”
Section: Discussionmentioning
confidence: 86%
“…(2) Liver extracts were always centrifuged at lOOOOOg for 60min before use of the supernatant for assay. This procedure should sediment particulate glucokinase activity (Berthillier et al, 1976) and also glucose-6-phosphatase (Hers et al, 1951). The latter can catalyse the phosphorylation of glucose with pyrophosphate as a phosphate donor (Nordlie & Lygre, 1966).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are several differences between particulate and soluble glucokinase. Rat liver particulate glucokinase does not cross-react immunologically with an antiserum to soluble glucokinase, nor does its activity change in the livers of diabetic or neonatal rats, unlike the activity of soluble glucokinase (Berthillier et al, 1976). Furthermore, full particulate glucokinase activity is only obtained when liver extracts are sonicated or treated with detergents (Berthillier et al, 1976;Wals & Katz, 1981).…”
mentioning
confidence: 94%
See 2 more Smart Citations